COGNITIVE FEATURES OF METAPHORS OF ENGLISH, RUSSIAN, AND UZBEK LANGUAGE (International Conference on Medical Science, Medicine and Public Health, 2025)
This article examines the cognitive features of a metaphor in English, Russian, and Uzbek languages using a comparative lens. It investigates the similarities and differences between these three languages using cognitive linguistic theory, focusing on metaphors' significance in conceptualizing abstract events, particularly the idea of "life." The study also looks at metaphorical tales in literary texts to see how cultural environment influences metaphorical thinking.